The emerging issue of cognitive disorders and dementia among migrants. (30th September 2020) - Canevelli, M; Lacorte, E; Cova, I; Cascini, S; Bargagli, A M; Giusti, A; Pomati, S; Pantoni, L; Vanacore, N
Abstract: Background: Due to population aging, people with a migration background are (and will be) increasingly exposed to the burden of chronic, age-related diseases. Specifically, the occurrence of dementia and cognitive disorders in this population of individuals can assume special clinical and public health relevance. The ImmiDem project (GR-2016-02364975) is aimed at characterizing the emerging phenomenon of cognitive disorders in migrants in Italy. Methods: The number of dementia and mild cognitive impairment (MCI) cases among migrants living in the extended European Union was calculated by applying the age- and gender-specific prevalence rates of these conditions to the population data of international migrants provided by Eurostat. A pilot survey was addressed to a representative sample of Italian centers for cognitive disorders and dementia (CCDDs) with the aim of collecting information on the number of migrants attending these services, the adopted diagnostic, and the possible barriers and resources in the provision of care. Results: Nearly 700, 000 cases of dementia and 680, 000 cases of MCI can be estimated in the migrant population living in Europe in 2018. Nevertheless, the number of migrants referred to the surveyed CCDDs was very low and was considered as stable over the last 5 years. Most of CCDDs reported the possibility of contacting cultural mediators and/or interpreters, while only a few reported the availability and regular use of translated and/or cross-cultural cognitive assessment tools. Conclusions: The data produced by the ImmiDem project allow a preliminary characterization of the emerging phenomenon of cognitive disturbances in the migrant population. The survey will be extended to all Italian dementia services (CDCD, day centers, residential structures). Activities aimed at identifying and promoting dedicated care pathways or good practices will also be conducted. Key messages: The clinical and epidemiological characterization of cognitive disorders occurring in migrants represent an emerging public health matter for Western countries. The onset of dementia in migrants can result in important clinical-diagnostic and healthcare complexities.